Fungal Periprosthetic Joint Infection in Total Knee Arthroplasty: A Systematic Review - Jakobs, Oliver (Orthop Rev (Pavia), 2015)
Fungal periprosthetic joint infection (PJI) is a rare but devastating complication following total knee arthroplasty (TKA). A standardized procedure regarding an accurate treatment of this serious complication of knee arthroplasty is lacking. In this systematic review, we collected data from 36 studies with a total of 45 reported cases of a TKA complicated by a fungal PJI. Subsequently, an analysis focusing on diagnostic, medicaments and surgical procedures in the pre-, intra- and postoperative period was performed. Candida spp. accounts for about 80% (36 out of 45 cases) of fungal PJIs and is therefore the most frequently reported pathogen. A systemic antifungal therapy was administered in all but one patient whereas a local antifungal therapy, e.g. the use of an impregnated spacer, is of inferior relevance. Resection arthroplasty with delayed re-implantation (two-stage revision) was the surgical treatment of choice. However, in 50% of all reported cases the surgical therapy was heterogeneous. The outcome under a combined therapy was moderate with recurrent fungal PJI in 11 patients and subsequent bacterial PJI as a main complication in 5 patients. In summary, this systematic review integrates data from up to date 45 reported cases of a fungal PJI of a TKA. On the basis of the current literature strategies for the treatment of this devastating complication after TKA are discussed.